MODELING THE DESIGN ACTIVITY OF A TEACHER OF TECHNICAL DISCIPLINES - Koeberlein-Kerler, Juergen (Problems of Engineer-Pedagogical Education, 2022)
The article considers the requirements of the modern educational environment to the professional activity of teaching staff and the need to plan their short- and long-term activities. These requirements activate pedagogical design as a type of activities of teaching staff. Examples of research into this question in works of various scientists are analyzed. Information on various theoretical and practical problems of design as subjects of scientific research is generalized. The skills that future teachers should develop within the training process, which will allow them to carry out design activities and form the basis of design competence, are characterized. The definitions of the concepts "design activity" by different authors are given and analyzed, among which the concept that is most expedient to the subject of our research is determined. Design activity is claimed to be inherent in any pedagogical worker, regardless of where they work. Characteristics of design activities are considered on the example of a future engineer-teacher, a vocational education teacher of technical disciplines. The necessity of developing pedagogical design skills of future engineers-teachers, teachers of technical disciplines in a higher education institution is substantiated. Examples of types of projects that can be developed in the system of vocational education are given. The comparative characteristics of pedagogical and didactic projects are carried out. The general structure of an activity of the engineer-teacher on didactic design is given; activity stages and elements of each of the stages are defined. On the basis of the general structure of didactic design activities, modeling of the design activity of the future engineer-teacher, the teacher of technical disciplines of a vocational education institution while designing a didactic project within a technical discipline course defined by the standard of professional education is carried out. The characteristic features of the organization of the educational process on the basis of the standards of vocational education, developed on the basis of the competence approach, are given. The clearly structured algorithm of the design activity for a didactic project in a technical discipline offered in the article allows adjusting students’ activities while performing similar tasks in the course of studying at an education institution and has practical value for teachers of the system of vocational education.